Evaluation of the Alignment of the Learning Process of the Elementary School Teacher Professional Education Program with Gagné's Learning Theory: An Analysis of Records - Yusnidar Yusnidar; Dwi Agus Kurniawan; Elza Triani; Miftahul Zannah Azzahra; Ahmad Mansur Nawahdani (International Journal of Elementary Education, 2025)
Improving the basic quality of education is highly dependent on the professional competence of teachers, one of which can be achieved through the Teacher Professional Education Program. However, there are concerns that the learning process in this program has not fully followed proven effective learning theories, such as Gagne's learning theory. This research aims to evaluate the alignment of the learning process in the Primary School Teacher Professional Education Program with Gagné's learning theory through analysis of learning recordings. Using a qualitative approach with a case study design, this research analyzed 3 learning recordings selected purposively. Data was collected through video observations and analyzed using Gagné's learning principles. The results of the analysis show that most of Gagné's steps were implemented well by students in the Primary School Teacher Professional Education Program, especially in getting attention, conveying learning objectives, and provoking memory. However, there are weaknesses in presenting content and strengthening concepts. This research provides recommendations for increasing the variety of learning media and providing more detailed feedback. The novelty of this research lies in the in-depth analysis of the application of Gagné's theory in the context of teacher professional education, offering practical guidance for educators to improve pedagogical competence.